2017
DOI: 10.1253/circj.cj-16-0633
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes and Prognostic Factors After Pericardiectomy for Constrictive Pericarditis in a Japanese Population

Abstract: Background: Constrictive pericarditis (CP) is characterized by impaired diastolic cardiac function leading to heart failure. Pericardiectomy is considered effective treatment for CP, but data on long-term clinical outcomes after pericardiectomy are limited. Methods and Results:We retrospectively investigated 45 consecutive patients (mean age, 59±14 years) who underwent pericardiectomy for CP. Preoperative clinical factors, parameters of cardiac catheterization, and cardiac events were examined. Cardiac events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
(17 reference statements)
2
15
0
Order By: Relevance
“…Our short- and long- term results are similar to those presented by other investigators [ 1 , 8 , 21 ]. However, some published reports indicated a significantly higher perioperative mortality; this may be due to differences in baseline patient characteristics as such studies often have a higher proportion of subjects classified as preoperative NYHA Class IV [ 2 , 5 8 , 11 , 14 , 24 ]. We find that there are a number of risk factors that affect survival after pericardiectomy, with the most significant being the presence of prior cardiac intervention, baseline chronic kidney disease with dialysis, and prior radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Our short- and long- term results are similar to those presented by other investigators [ 1 , 8 , 21 ]. However, some published reports indicated a significantly higher perioperative mortality; this may be due to differences in baseline patient characteristics as such studies often have a higher proportion of subjects classified as preoperative NYHA Class IV [ 2 , 5 8 , 11 , 14 , 24 ]. We find that there are a number of risk factors that affect survival after pericardiectomy, with the most significant being the presence of prior cardiac intervention, baseline chronic kidney disease with dialysis, and prior radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In a 24-year experience on pericardiectomy in patients with constrictive pericarditis, based on Kaplan-Meier survival curves demonstration, Szaboa et al [36] have confirmed poor prognosis of post-irradiation constrictive pericardiectomy and shown better and comparable long-term survival after in other etiologies as idiopathic tuberculosis myocardial infarction, and uremia; the author noted no survival after 5 years with post-radiation constrictive pericarditis; it is widely accepted radiation etiology is a negative factor affecting long-term survival results as well indicated by Nishimura in Japanese population [37] and Avgerinos et al [38]. On his study related to 46 patients with a mean age of 59 years and various classic etiologies, Nishumuna et al [37] have described the very high severity of radiation etiology with death within only 1 year after pericardiectomy confirming overall literature results.…”
Section: Late Outcomesmentioning
confidence: 85%
“…Hypoalbuminemia was the major postoperative complication possibly because of the negative nitrogen balance after surgery. The incidence of low cardiac output was also high enough to warrant attention, because it was proven to be the major contributor to in-hospital death in other studies [3,22,23] . In our study, postoperative complication was seemed to be associated with symptom duration, preoperative NYHA functional class, pulse rate, preoperative CVP, pleural effusion and serum sodium, while multivariate analysis eventually proved that poor preoperative NYHA functional class and high preoperative CVP were independent risk factors of postoperative complication, which might provide a valuable reference for preoperative preparation and risk evaluation.…”
Section: Discussionmentioning
confidence: 99%